2018
DOI: 10.1016/j.ajhg.2018.07.016
|View full text |Cite
|
Sign up to set email alerts
|

A Multiplex Homology-Directed DNA Repair Assay Reveals the Impact of More Than 1,000 BRCA1 Missense Substitution Variants on Protein Function

Abstract: Loss-of-function pathogenic variants in BRCA1 confer a predisposition to breast and ovarian cancer. Genetic testing for sequence changes in BRCA1 frequently reveals a missense variant for which the impact on cancer risk and on the molecular function of BRCA1 is unknown. Functional BRCA1 is required for the homology-directed repair (HDR) of double-strand DNA breaks, a critical activity for maintaining genome integrity and tumor suppression. Here, we describe a multiplex HDR reporter assay for concurrently measu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
117
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(121 citation statements)
references
References 36 publications
4
117
0
Order By: Relevance
“…Recently, two saturation mutagenesis-based high-throughput approaches evaluated the impact of 1,056 and 3,893 BRCA1 variants in exons 2-7 and 15-24, respectively [59,60]. Each study used a distinct biological role of BRCA1.…”
Section: Functional Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, two saturation mutagenesis-based high-throughput approaches evaluated the impact of 1,056 and 3,893 BRCA1 variants in exons 2-7 and 15-24, respectively [59,60]. Each study used a distinct biological role of BRCA1.…”
Section: Functional Assaysmentioning
confidence: 99%
“…Each study used a distinct biological role of BRCA1. Starita and colleagues [61] interrogated the impact of alteration on the amino-terminus of BRCA1 on its role on Homology-directed Repair (HDR) while Findlay and colleagues [59] based their assay on the requirement of a functional BRCA1 for viability in a near-haploid human cell line (HAP1). These studies demonstrated the feasibility of this approach and reported an excellent agreement with the available clinical data in ClinVar database [59].…”
Section: Functional Assaysmentioning
confidence: 99%
“…While thousands of BRCA1 VUSs have been assessed by recently developed high-throughput functional assays 15,16,17 , a few hundred BRCA2 variants have been evaluated by a conventional functional assay for BRCA2 , the HDR assay 18,19 . The HDR assay has three issues requiring improvement: (i) the throughput is quite low, (ii) it uses a hamster cell line with transient expression of BRCA2 cDNA, and most importantly, (iii) it can evaluate only variants in the DNA-binding domain 14,20 .…”
Section: Introductionmentioning
confidence: 99%
“…The landscape of functionally characterized variants in BRCA1 has dramatically increased because of three major analyses. Starita et al 2 , measured the impact of 1056 N-terminal variants on the homologous recombination DNA repair activity of BRCA1. Findlay et al 3 , exploited the essentiality of BRCA1 for cell survival by used a saturating genome editing approach in HAP1 cells to evaluate nearly 4,000 SNVs (n=1837 distinct missense).…”
Section: Introductionmentioning
confidence: 99%